PURCHASE MANAGEMENT: strategies used as a way to reduce costs - Anselmo, Amauri; Antônio Alves de Sousa Junior, Marco (Revista Interface Tecnológica, 2021)
Some purchasing strategies can be used so that the costs of organizations are reduced and thus reflect, in increasing profits, a factor that can significantly contribute to investments and, consequently, to the development of companies. The purpose of this article is to highlight strategies to be used by the purchasing department as a way to reduce costs within organizations, a factor that positively impacts its growth. For this study, a bibliographic survey was carried out on books, academic articles and publications that bring studies on possible strategies used by the purchasing department as a way to reduce costs. The inclusion criterion was based on the date of publication, last fifteen years, and the language, written in Portuguese. The literature points out that reducing costs is an important strategy and that in addition to increasing profits, it generates good results for the company, factors that add up to its growth and development.